Winter climate signal in boreal clastic-biogenic varves: a comprehensive analysis of three varved records from 1890 to 1990 AD with meteorological and hydrological data from Eastern Finland. (2nd October 2017) - Saarni, Saija; Lensu, Anssi; Tammelin, Mira; Haltia, Eeva; Saarinen, Timo
Abstract: Clastic-biogenic varves are widely used for reconstructing past climate: in boreal environments, the accumulation of minerogenic clasts on the lake floor is generally considered a proxy for past variations in spring floods reflecting previous winter conditions. However, the physical mechanisms behind this winter climate sensitivity and the influence of catchment type on the varve formation are not fully investigated. Here, we present a winter climate record inferred from the clastic laminae of three lakes located on the region of fine-grained tills in Eastern Finland spanning from AD 1890 to 1990. The minerogenic varve data are compared with instrumental meteorological and hydrological time series in order to investigate the physical link between winter and spring climate and minerogenic matter accumulation. Our analyses reveal that the climate-catchment mechanisms operating in the region of fine-grained tills differ crucially from previously described climate catchment interactions on sand moraine-dominated catchments in Finland, where the maximum river discharge in spring controls the clastic lamina formation. However, in contrast to earlier boreal varve records from Central Finland, the clastic lamina formation in the studied region correlates negatively with spring temperatures and winter precipitation. This could be an artefact of varying catchment dynamics but also related to the regional climate. The lakes surrounded by catchments characterized by fine-grained tills are more sensitive to cold and dry winters. The differences in the sensitivity of varve characteristics to climate, highlights the importance of understanding the catchment dynamics in detail in order to better understand climatic forcing.